The Meaning of the Lamaholot Regional Language Based on the Thoughts of Ludwig Wittgenstein in the Philosophy of Language - Koten, Philipus Ola; Nuka, Ewaldus; Fallo, Yohanes Risaldo; Sila, Gregorius; Bureni , Stefano Rivaldy Batista (Jurnal Indonesia Sosial Sains, 2026)
This research aims to analyze the meaning of the Lamaholot regional language based on the perspective of Ludwig Wittgenstein's language philosophy, especially the concept of meaning in use and language games, as well as interpret the sacred phrase "Boru Tana Bojang Kebo Kili Batu" as a representation of the socio-cultural reality of the Boru people in East Flores. The research method used was a descriptive qualitative approach with literature studies, where primary data comes from Wittgenstein's works, especially Philosophical Investigations, and secondary data from various literature related to the Lamaholot language, culture, and philosophy of language. The data analysis technique was carried out interpretively by relating the use of language in the context of traditional ceremonies and social interaction of the Lamaholot community with Wittgenstein's framework of thought. The novelty of this research lies in the integration of two periods of Wittgenstein's thought to uncover layers of regional language meanings that have not previously been studied philosophically. The results of the study showed that the Lamaholot language not only functions as a means of communication, but also as a symbol that describes reality (image theory) and has a meaning determined by its use in various socio-cultural contexts (language games). The phrase "Boru Tana Bojang Kebo Kili Batu" contains philosophical values about fertility, unity, and harmony that are reflected in people's lives. This research contributes to the development of the study of language philosophy in the local context and provides recommendations for efforts to preserve regional languages as intangible cultural heritage.